Von Willebrand factor contribution to pathophysiology outside of von Willebrand disease. (19th November 2018) - Mojiri, Anahita; Alavi, Parnian; Jahroudi, Nadia
Abstract: VWF is a procoagulant protein that plays a central role in the initiation of platelets aggregate formation and thrombosis. While von Willebrand disease has long been known to result from qualitative and quantitative deficiencies of VWF, it is recently that contribution of elevated levels of VWF to various pathological conditions including thrombosis, inflammation, angiogenesis, and cancer metastasis has been appreciated. Here, we discuss contribution of elevated levels of VWF to various thrombotic and nonthrombotic pathological conditions.